Manichaeism: encounters with death studies in the material, spiritual and parabolic body - Towers, Susanna (Turnhout, Belgium Brepols, 2024)
"Born in Persian Mesopotamia in the year 232 CE, the self-proclaimed prophet Mani promulgated a dualist faith that rapidly spread throughout the Roman Empire, Central Asia and China. This monograph comprises a series of studies of the Manichaean conceptualization of death and the afterlife in the context of Manichaean soteriology, eschatology and anthropology. Material, documentary and liturgical evidence is analysed to enrich knowledge of Manichaean funeral ritual and mourning practice. The book explores the thematic symbolism of the corpse in Manichaean parabolic literature, offering fresh interpretations and exploring the influence of Buddhist teachings on the impermanence of the body, karma and metempsychosis."
Literaturverzeichnis: Seite [303]-338
Archivierung/Langzeitarchivierung gewährleistet